Candida albicans Expresses a Focal Adhesion Kinase-Like Protein That Undergoes Increased Tyrosine Phosphorylation upon Yeast Cell Adhesion to Vitronectin and the EA.hy 926 Human Endothelial Cell Line - Santoni, Giorgio (American Society for Microbiology, 2002)
The signaling pathways triggered by adherence of Candida albicans to the host cells or extracellular matrix are poorly understood. We provide here evidence in C. albicans yeasts of a p105 focal adhesion kinase (Fak)-like protein (that we termed CaFak), antigenically related to the vertebrate p125Fak, and its involvement in integrin-like-mediated fungus adhesion to vitronectin (VN) and EA.hy 926 human endothelial cell line. Biochemical analysis with different anti-chicken Fak antibodies identified CaFak as a 105-kDa protein and immunofluorescence and cytofluorimetric analysis on permeabilized cells specifically stain C. albicans yeasts; moreover, confocal microscopy evidences CaFak as a cytosolic protein that colocalizes on the membrane with the integrin-like VN receptors upon yeast adhesion to VN. The protein tyrosine kinase (PTK) inhibitors genistein and herbimycin A strongly inhibited C. albicans yeast adhesion to VN and EA.hy 926 endothelial cells. Moreover, engagement of αvβ3 and αvβ5 integrin-like on C. albicans either by specific monoclonal antibodies or upon adhesion to VN or EA.hy 926 endothelial cells stimulates CaFak tyrosine phosphorylation that is blocked by PTK inhibitor. A role for CaFak in C. albicans yeast adhesion was also supported by the failure of VN to stimulate its tyrosine phosphorylation in a C. albicans mutant showing normal levels of CaFak and VNR-like integrins but displaying reduced adhesiveness to VN and EA.hy 926 endothelial cells. Our results suggest that C. albicans Fak-like protein is involved in the control of yeast cell adhesion to VN and endothelial cells.